2018
DOI: 10.1155/2018/8561458
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Diversity and Geographic Differentiation of the Wild Soybean in Northeast China Based on Nuclear Microsatellite Variation

Abstract: In this study, the genetic diversity and population structure of 205 wild soybean core collections in Northeast China from nine latitude populations and nine longitude populations were evaluated using SSR markers. A total of 973 alleles were detected by 43 SSR loci, and the average number of alleles per locus was 22.628. The mean Shannon information index (I) and the mean expected heterozygosity were 2.528 and 0.879, respectively. At the population level, the regions of 42°N and 124°E had the highest genetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
2
3
0
2
Order By: Relevance
“…It seems that, the diversity of populations has not relation with the geographical pattern. The independence of genetic diversity from geographic diversity can be seen in other reports of this type of research [13,14]. As shown in the figure, the majority of the accessions are located at relatively the same genetic distance, and only a few of them, which are mainly related to the Northwestern parts, are at a relatively far distance.…”
Section: Resultssupporting
confidence: 58%
“…It seems that, the diversity of populations has not relation with the geographical pattern. The independence of genetic diversity from geographic diversity can be seen in other reports of this type of research [13,14]. As shown in the figure, the majority of the accessions are located at relatively the same genetic distance, and only a few of them, which are mainly related to the Northwestern parts, are at a relatively far distance.…”
Section: Resultssupporting
confidence: 58%
“…Similar studies reported by Hipparagi et al (2017) the heterozygosity observed in the present study was much lower than the value reported by the other researchers but some others studies reported low heterozygosity in the crop, for example Song et al (2013) (0.045) and Li et al (2008) (0.014). The Shannon's information index of 0.894 in the present study was lower than the results obtained by Zhao et al (2018) who reported Shannon's information index of 2.528, but also reported fixation index of 0.987 which was comparable to the one obtained in this study. The results of Shannon's information index and fixation index revealed a shift from Hardy-Weinberg equilibrium, again indicating the presence of moderate genetic variation among the genotypes which could be attributed to the fact that these genotypes are sharing GC001 and Duiker as common parental lines (Table 1).…”
Section: Discussionsupporting
confidence: 61%
“…Nghiên cứu về sán lá đơn chủ trên cá da trơn dựa trên đặc điểm hình thái và di truyền được tiến hành ở hầu hết các châu lục: Châu Á như Thái Lan (Lim, Lerssutthichawal, 1996), Ấn Độ (Agrawal et al, 2016;Verma et al, 2016aVerma et al, , 2017aVerma et al, , 2017bPandey, Agrawal, 2017;Gusev, 1976;Rizvi, 1971), Indonesia (Pariselle et al, 2001(Pariselle et al, , 2002(Pariselle et al, , 2003(Pariselle et al, , 2004(Pariselle et al, , 2006, ở Châu Âu như Nga (Lim et al, 2001) và Nam Mỹ như Peru (Mendoza-Palmero et al, 2012) và Brasil (Negreiros et al, 2019. Ở Việt Nam, các nghiên cứu chủ yếu được tiến hành trên một số vật chủ bao gồm cá lóc (Channa striata), cá trê trắng (Clarias batrachus), cá lăng nha (Hemibagrus wyckioides), và cá tra (Pangasianodon hypophthalmus) ở nhiều vùng trong nước (Hà Ký, Bùi Quang Tề, 2007;Vũ Đặng Hạ Quyên et al, 2014;Nguyễn Thị Thu Hằng, Đặng Thị Hoàng Oanh, 2012, 2015, 2018Nguyễn Thị Thu Hằng, 2017), tuy nhiên chưa có nghiên cứu về các loài sán lá đơn chủ ở khu vực Đắk Lắk.…”
Section: Giới Thiệuunclassified
“…Nhóm nghiên cứu của Ciftci, Okumus (2003) cho thấy sự biến động di truyền có liên quan đến khoảng cách địa lý và thời gian di cư đối với quần thể cá trong khảo sát di truyền quần thể dựa trên phân tích chỉ thị phân tử phụ thuộc vào giá trị phân tách di truyền fst. Ghi nhận tương tự về sự phân tách khu vực địa lý khảo sát trên các loài thực vật trong nghiên cứu Zhao et al (2018) cũng cho thấy sự đa dạng di truyền và cấu trúc quần thể đối với 205 loài thực vật từ 9 tọa độ khác nhau bao gồm 84 khu vực Trung Quốc. Nhóm nghiên cứu phát hiện sự phân bố ở các khu vực địa lý ảnh hưởng rất lớn đến sự khác biệt di truyền của từng quần thể thực vật, cụ thể là phần trăm khác biệt trong quần thể là > 90%.…”
Section: Mối Quan Hệ Phát Sinh Loài Của Các Loài Sán Lá đơN Chủ Trên ...unclassified